Inhibition of Streptococcus mutans Biofilm Formation and Virulence by Lactobacillus plantarum K41 Isolated From Traditional Sichuan Pickles - Zhang, Guojian; Lu, Miao; Liu, Rongmei; Tian, Yuanyuan; Vu, Viet Ha; Li, Yang; Liu, Bao; Kushmaro, Ariel; Li, Yuqing; Sun, Qun (Frontiers in Microbiology, 2020)
Among cariogenic microbes, Streptococcus mutans is considered a major etiological pathogen of dental caries. Lactobacilli strains have been promoted as possible probiotic agents against S. mutans, although the inhibitory effect of Lactobacilli on caries has not yet been properly addressed. The objective of this study was to screen Lactobacillus strains found in traditional Sichuan pickles and to evaluate their antagonistic properties against S. mutans in vitro and in vivo. In the current study, we analyzed 54 Lactobacillus strains isolated from pickles and found that strain L. plantarum K41 showed the highest inhibitory effect on S. mutans growth as well as on the formation of exopolysaccharides (EPS) and biofilm in vitro. Scanning electron microscopy (SEM) and confocal laser scanning microscope (CLSM) revealed the reduction of both EPS and of the network-like structure in S. mutans biofilm when these bacteria were co-cultured with strain L. plantarum K41. Furthermore, when rats were treated with strain L. plantarum K41, there was a significant reduction in the incidence and severity of dental caries. Due to K41’s origin in a high salinity environment, it showed a high tolerance to acids and salts. This may give this strain an advantage in harsh oral conditions. Results showed that L. plantarum K41 isolated from traditional Sichuan pickles effectively inhibited S. mutans biofilm formation and thus possesses a potential inhibitory effect on dental caries in vivo.